Promoting exports of low-aflatoxin groundnut from Malawi - Edelman, Brent; Aberman, Noora-Lisa (International Food Policy Research Institute, 2015)
Malawi’s National Export Strategy is built on the premise that the promotion of exports and domestic value addition can contribute to economic growth and poverty reduction in a meaningful way. Groundnut shows particularly high potential because regional de-mand is strong and Malawi’s farmers are already quite familiar with improved methods for growing the crop (Government of Malawi, 2013). In spite of institutional weaknesses that make exporting te-dious and time consuming (Aberman & Edelman, 2014), groundnut exports volumes grew by 18 percent per year between 2004 and 2014 (International Trade Centre, 2014; Malawi Revenue Authority, 2014). However, high levels of aflatoxin contamination threaten to disrupt these positive trends: 49 percent of groundnut sold in Malawi’s local markets and 60 percent of those sold in shops and supermarkets were found to have aflatoxin levels exceeding those considered safe for human consumption (Emmott & Stephens, 2014).